A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera) - Hugel, Sylvain; Desutter-Grandcolas, Laure (Zootaxa, 2018)
Most high volcanic islands of Lesser Antilles harbor one single genus of Anostostomatidae: Rhumosa n. gen: Rhumosa bolognei n. gen. n. sp. in Guadeloupe, Rhumosa macoucheriei n. gen. n. sp. in Dominica, Rhumosa depazei n. gen. n. sp. in Martinique, Rhumosa admiralrodneyei n. gen. n. sp. in Saint Lucia, Rhumosa captainblighei n. gen. n. sp., in Saint Vincent. These species are restricted to well preserved rainforests; species from northern islands apparently occurring at higher elevation than species of southern islands. The distribution and generic position of Rhumosa n. gen. species is discussed, as well as the generic position of Lutosa cubaensis (Haan, 1843).